the Legal prosecution between the Algerian family law and Islamic Fiqh - Boubendir, Abdeldjallil (Journal of Human Sciences, 2020)
The Algerian legislator set the provisions of the legal (sahria)prosecution by the articles of the family law. This system principally aims to protect the funds of a young age minor or one of the hindrance of the symptoms of eligibility. The legislator already provided three forms : Guardianship,Trusteeship and submission or wardship as it is very often refered to in the Islamic fiqh (jurisprudence).The Algerian legislator derived a set of provisions that are relating to personal status or family law from the islamic jurisprudence therefore, this research looks forward to highlighting the most important differences between the provisions of Sharia prosecution which is stipulated by the Algerian legislator and what is corresponding in the Islamic jurisprudence with its four major doctrines.